RE-CONCEPTUALISING LEADERSHIP FOR EFFECTIVE PEACEMAKING AND HUMAN SECURITY IN AFRICA (The Strategic Review for Southern Africa, 2020)
This article explores the meaning of peace and human security from theperspective of the individual — the presumed referent point of security— and examines responses to armed conflict, a leading source of insecurity for African peoples. It identifies inherent flaws in approaches to conflict in Africa and looks to a different field — that of leadership — for a more effective formula for peacemaking. In the absence of a framework that can effectively end the cycle of conflict relapse in Africa,the paper argues that an alternative framing of leadership is needed; and that alternative leadership approaches to dealing with conflict andinsecurity offer a chance for stable peace and human security. It suggests that an expanded perspective on leadership provides a basis for exploring interventions that can potentially alter peacemaking discourses as well as the terrain in which peacemaking takes place. The article therefore asks what a focus on the individual as the referent point of security means if and when viewed from the perspective of a collection of individuals. In this regard, it presents emerging perspectives from a study of young Africans on leadership programmes in a classroom setting and attempts to extrapolate them to wider societal settings. It then explores how a different perspective of leadership might serve as a facilitator of peace and human security in Africa, drawing examples from past and on-going situations of armed conflict in Africa.